Weeding out deviant workplace behaviour in downsized organizations: the role of emotional intelligence and job embeddedness - Mohd Yusof, Mastura; Jo, Ann Ho; Ng, Serene Siew Imm; Zawawi, Dahlia (Asia Business Research Corporation, 2019)
While job insecurity has been widely studied across various contexts, the empirical study within the Malaysian context remained scarce. This study was undertaken to investigate the effect of job insecurity on deviant workplace behaviour on employees from retrenching organizations. This study also explored the effects of emotional intelligence and job embeddedness as moderating variables. Respondents were selected from retrenching organizations located in Johore, Penang and Selangor as these three states had the highest number of retrenchment cases in the country. Hypotheses testing was carried out using partial least squares structural equation modelling (PLS-SEM), the SmartPLS version 2.0. Overall, the results showed that job insecurity was negatively related to affective commitment and positively related to job-related tension. No relationship was detected between affective commitment and deviant workplace behaviour; however job-related tension correlated positively to deviant workplace behaviour. There was also a significant moderating influence of emotional intelligence on affective commitment and deviant workplace behaviour as well as on the relationship between job-related tension and deviant workplace behaviour. In addition, job embeddedness moderated the relationship between job- related tension and deviant workplace behaviour. The implications of the results to both theory and practice are discussed in this paper.